Development of Electronic Pocketbook Media on Plant-like Protist for Class X Senior High School - Qairunisa, Maya Rahmadanty; Daningsih, Entin; Candramila, Wolly (Integrated Science Education Journal, 2024)
Purpose of the Study: This study aimed to develop and validate an innovative electronic pocketbook on plant-like protists, designed for use by class X Senior High School students. The pocketbook integrates real-world examples of phytoplankton research from the Teluk Nibung River, offering a modern and engaging learning tool that enhances students' understanding of plant-like protists. Methodology: The research employed a Research and Development (R&D) method, encompassing three stages: pre-production, production, and post-production. Validation was conducted using questionnaire sheets with a Guttman scale, assessed by two lecturers. Additionally, media validation sheets, covering format, content, language, and practicality, were evaluated using a Likert scale by two lecturers and three biology teachers. Main Findings: The electronic pocketbook contains comprehensive material on plant-like protists, enriched by real phytoplankton research results from the Teluk Nibung River. The pocketbook includes essential components such as cover, preface, instructions, table of contents, material content, bibliography, glossary, and author profile. The validation results yielded a CVI value of 1.00, indicating that the pocketbook is valid and suitable as a learning medium for plant-like protists in class X biology. Novelty/Originality of this Study: This study presents a unique approach by integrating phytoplankton research into the curriculum through a digital format. The electronic pocketbook offers flexibility by being accessible both online and offline, and can be downloaded using free applications, providing students with a practical and innovative tool for learning. The incorporation of real-world data not only enhances engagement but also bridges the gap between theoretical knowledge and field research.